Effect of dental age on edible and non-edible meat yield characteristics of indigenous beef cattle - Islam, MS; Hossain, MM; Akhter, S; Al Noman, MA; Goswami, PK; Hasan, MM; Mustari, A; Hashem, MA (Meat Research, 2022)
The objective of this study was to know the effect of dental age on the meat yield characteristics of indigenous beef carcasses. This experiment was conducted with five (5) treatments (T1, T2, T3, T4 and T5) where T1 = 0 Permanent incisor, T2 = 2 Permanent incisors, T3 = 4 Permanent incisors, T4 = 6 Permanent incisors, T5 = 8 Permanent incisors having ten (10) replications. From the experiment it shows that live and hot carcass weight increased significantly in T1 and T2 compared to T3, T4 and T5. Cold carcass weight (CCW) increased significantly with the advancement of dental maturity. KPH% was highest in T4 and lowest in T3 whereas round and loin% were highest in T4 and T3 respectively but both are lowest in T1. Lungs with trachea, liver and kidney weight% were significantly higher in T1 than others group. In conclusion, maximum live weight gain and hot carcass weight were achieved in the dental age groups of two to four permanent incisors.